2000
DOI: 10.4315/0362-028x-63.10.1359
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Effect of Rosemary Extracts

Abstract: A rosemary extract commercially exploited (Oxy'less) as an antioxidant of lipids in foods was dissolved in ethanol (100 mg/ml), and the solution was tested against foodborne microorganisms. For gram-positive bacteria, the MIC of the ethanolic solution was 1% for Leuconostoc mesenteroides, 0.5% for Listeria monocytogenes, 0.5% for Staphylococcus aureus, 0.13% for Streptococcus mutans, and 0.06% for Bacillus cereus. It slowed the growth of Penicillium roquefortii and Botrytis cinerea. Up to 1% of the ethanolic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
129
2
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(146 citation statements)
references
References 18 publications
9
129
2
2
Order By: Relevance
“…Previously studied natural antimicrobials in meat products include bacteriocins, lactoferrin, lysozyme, spices, essential oils and variety plant extracts. Antibacterial activity of rosemary extract (Del Campo et al 2000), garlic extract (Tsao and Yin 2001), grape fruits extract in fish (Cho et al 1990), capsicum extract in raw beef (Monica et al 2003), oregano essential oils in sheep meat (Govaris et al 2010) have been reported. The antimicrobial activity of many plant extracts, traditional spices and essential oils is well documented (Ahmad and Beg 2001;Naz et al 2007;Shan et al 2007;Burt 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Previously studied natural antimicrobials in meat products include bacteriocins, lactoferrin, lysozyme, spices, essential oils and variety plant extracts. Antibacterial activity of rosemary extract (Del Campo et al 2000), garlic extract (Tsao and Yin 2001), grape fruits extract in fish (Cho et al 1990), capsicum extract in raw beef (Monica et al 2003), oregano essential oils in sheep meat (Govaris et al 2010) have been reported. The antimicrobial activity of many plant extracts, traditional spices and essential oils is well documented (Ahmad and Beg 2001;Naz et al 2007;Shan et al 2007;Burt 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Its essential oil is used therapeutically and balneologically. Rosemary contains a large number of compounds responsible for its antioxidant, anti-inflammatory, anti-mutagenic, anti-carcinogenic, chemo-preventive, antimicrobial, and anti-viral activities [4][5][6][7][8][9][10] . Also, an induction of NGF (nerve growth factor) in human glioblastoma cells using rosemary extract has been described 11 …”
Section: Introductionmentioning
confidence: 99%
“…Besides, some reported that a number of compounds contained in the extracts of R. officinalis revealed antibacterial and antifungal properties [20,21].…”
Section: Discussionmentioning
confidence: 99%